ANALISIS PEMBINGKAIAN BERITA HUKUMAN MATI BAGI PELAKU PEMERKOSAAN HERRY WIRAWAN PADA MEDIA ONLINE KOMPAS.COM - Hamzah Azwan Has (2024)
This research examines the online mass media Kompas.com in framing news on the case of sexual assault at a boarding school in Bandung by the perpetrator Herry Wirawan, along with the death penalty imposed on the perpetrator. This qualitative research employs the framing analysis method by Zhongdang Pan and Gerald M. Kosicki to analyze news published by Kompas.com regarding the case of sexual assault at a boarding school in Bandung by the perpetrator Herry Wirawan, along with the death penalty imposed on the perpetrator. The results of this research found that Kompas.com framed the issue by emphasizing that the death penalty given to the perpetrator is appropriate, and underscored the importance of siding with the victims of sexual violence by advocating for their rights and demanding that all the rights of the victims be fulfilled.